TWO PICTORIAL DOCUMENTS FROM THE COLONIAL PERIOD IN MEXICO (Bulletin of the Museum of Natural History, University of Oregon, 2019)
This brief report concerns two colonial-period picture documents from Mexico that are now in the possession of the Museum of Natural and Cultural History at the University of Oregon. Both concern historical matters of geographical import, both are termed mapas (“maps” in Spanish) but most strongly represent political statements.The first of these treated, identified as the Mapa de Cuauhtlantzinco, is apparently one of at least a half-dozen known copies, or partial copies, of an older document now unknown, and concerns especially people said to represent the town of Cuauhtlantzinco, which is located on the central Mexican highlands somewhat more than one hundred kilometers (62 miles) southeast of the heart of modern Mexico City. The second, now designated the Mapa de San Andrés Mixtepec is evidently a single, original document that directs itself to the history of a small settlement in the state of Oaxaca, and at a point located well over four hundred kilometers (249 miles) southeast of Mexico City, and more than three hundred fifty kilometers (217 miles) from Cuauhtlantzinco. Both of these mapas are of evident interest to local inhabitants of the two areas, which led the museum some years ago to gift photographic copies to people of these areas, which were delivered in Mexico through the good offices of a museum colleague, Dr. Stephanie Wood, of the University of Oregon. The first of these towns was Cuauhtlantzinco (on modern maps spelled Cuautlancingo) which led a local resident and student, Alberto Sarmiento Tepoztecatl (his surnames repeating two of those connected historically to the Mapa de Cuauhtlantzinco, as will be seen in Chapter 2) to visit the University of Oregon in the fall of 2002 and present a talk about the local mapa to an audience in the museum. The second (largely a matter of bad roads) was delivered not to the very rural town of San Andrés Mixtepec but to a regional alternative, the Francisco de Burgoa Library in Oaxaca City (capital of the state of Oaxaca), a library with affiliations to the Museum of Oaxacan Cultures as well as to the Universidad Autónoma Benito Juarez, both located in the state capital.As a pair, the documents—clearly of import for local aspects of Mexican post-colonial history—represent relatively untypical properties for holdings of this Oregon museum, so it seems well to begin with a brief history of how they came to be in the museum collection, and to summarize efforts made to determine precisely both what it is they represent—in a historical sense—and also the ways they can be seen to relate to the time and conditions of their Mexican places of named relationship. To approach this, Chapter 1 unwinds to provide information regarding the comparatively recent discovery of the documents within the museum and then summarizes research that revealed how they came to the institution. It goes on to discuss the specific geographical areas and ethnic regions of Mexico to which the documents each relate and adds basic information regarding the substantial differences between the mapas in construction and physical appearances and then of their apparently much smaller differences in probable dates of actual creation.Following this, Chapters 2 and 3—each of them devoted to a separate document—will delve at least superficially into the specific historical and ethnic backgrounds against which the documents themselves should be viewed, considering their differing geographical sources within Mexico. Each of these documents also focuses especially on matters of concern to aboriginal people of Mexico, rather than on those of overriding concern to their new colonial Spanish masters. As historical details emerge regarding each document and its milieu, questions can be raised as to why they were composed and completed at the dates that seem indicated by the evidence—dates that in both cases are more than a century after the actual Spanish conquest of Mexico was brought to completion.Chapter 4, then, provides further examinations of historical details that bear strongly on these questions— especially on just why the documents were created at the time or times in which they evidently emerged. Finally, although there will be no attempt in this brief guide to present complete and fully satisfactory color reproductions of either of the documents, portions of them will be presented in hopes of stimulating interest in obtaining more direct views of the documents themselves. In later pages, additional information pertinent to each of the documents will also include relevant addresses of materials on the University website.